Estímulos proximais e distais: as críticas de Davidson a Quine - Naidon, Karen Giovana Videla da Cunha (2012)
There are approximate thirty years, started a debate among philosophers W. V. O. Quine and D. Davidson about where it should be located in the causal chain speaking- world, the element that determines the empirical meaning of observation sentences - henceforth will call this element of "stimulus." According to Quine, who supports what might be called the "proximal conception," such stimulus would be located on the sensory surface speaker, ie, in a position close to him in this causal chain - proximal stimulus -; Davidson, on the other hand, criticizes the proximal conception, because it would not be able to explain the public nature of language and he suggests Quine to abandon the proximal conception in favor of distal conception, sustained by himself, according to which such a stimulus would be located in own objects and events about which the sentences speak, ie, in a position farther from the speaker - distal stimulus. Despite the suggestion of Davidson, Quine insists until the end of his work in not officially sustain the distal conception, introducing, however, some modifications in its conception in order to escape the criticism proceeded by the author. Given this di-vergence between the two authors, this work aims to carry out the reconstruction and evaluation of this debate. It should be noted, first of all, that Quine is a philosopher very systematic and his theses are closely interconnected, so it is necessary a more general overview of his philosophy whenever one want to understand a particular problem that is inserted in it, otherwise prejudice the proper understanding of it. Therefore, this work will be divided into two main parts: the first one will be reserved for the attempt to situate the central problem that it will be examined in the wake of broader Quinean philosophy as a whole, while the second part will be devoted to the reconstruction of the debate. The conclusion reached is that the final formulation of the conception of Quine can be considered as satisfactory solution of many problems of the initial formulation of proximal conception since we follow the suggestion of Lars Bergström and understand that the meaning of a observation sentence must consist of a subject s dispositions to assent and dissent to sentence, instead of identifying the meaning with set of proximal stimuli that the speaker ties to sentence. Furthermore, though it may be possible to raise objections to the Quine s final solution, it may be considered more appropriate solution to the problems of proximal conception since compared to the suggestion made by Davidson, because the adoption of conception distal would not be satisfactory for Quine s philosophical purposes.